PENAMBAHAN BUBUK ALGINAT (Sargassum sp) TERHADAP NILAI KESUKAAN BAKSO IKAN LELE (Clariidae batrachus) - Rahmad Yliandri; Sutrisno Adi Prayitno (Universitas Muhammadiyah Gresik, 2024)
Seaweed is a plant that has many benefits so it has the potential to be developed. The advantage of seaweed is that it is very economically abundant and very attractive as a food ingredient. The quality and potential of algae make it very popular in various countries around the world, apart from that, algae as a processed product and dried algae are widely exported. Using seaweed as an additional ingredient in making fish meatballs can increase the nutritional value and fiber content of meatball products. Final product data analysis was carried out using descriptive methods based on test results of selected products carried out on panelists. The average result of proximate testing of the final product is a water content of 61.54% with a maximum of 70% SNI 2354.2 2015 standard, an ash content of 1.07%. The SNI 2354.1-2010 standard is a maximum of 2.5% so that the ash content in good catfish meatballs does not exceed the SNI 2354.1-2010 standard regarding quality requirements, namely a maximum of 2.5%, the average fat content is 0.64% with the 2017 SNI 2354.3 standard. A maximum of 0.72%, the results of testing the fat content in catfish meatballs have a good and safe fat content in accordance with SNI 2354.3-2017, a protein content of 7.86%, the SNI standard of at least 7 fish protein levels is good. Carbohydrates 28.86%. regarding quality requirements for meatball products, namely a minimum of 1.5%. The average results of microbiological testing are total plate number (ALT) of 3.6 x 10³ colonies/g with a maximum standard of 102 -105 colonies/g and the average value of Staphylococcus aureus is <10 colonies/g with standard SNI 2333.3- 2015 with a maximum of 102 x 103 colonies/g.